Canfranc biology platform: exploring life in cosmic silence - Hernández-Antolín, Rebecca; Cid-Barrio, Laura; Peña-Garay, Carlos (Frontiers in Physics, 2024)
Deep underground laboratory infrastructures have extensively been used for exploring rare events, such as proton decay, dark matter searches or neutrino interactions, taking advantage of their large muon flux reduction. However, only very few investigations have evaluated the effects of low background radiation environments on living organisms. With this purpose, the Canfranc Underground Laboratory (LSC) launched the Biology Platform in 2021, which provides lab space for approved biology experiments. Two identical laboratories have been built (underground and on surface) to replicate biology experiments under the same conditions, with the main difference being the cosmic radiation background. The access protocol to use the LSC facilities includes two open calls per year and assigned time windows for executing the experimental program, which led to the first eight approved and already running experiments. We describe the scientific program of the Canfranc Biology Platform, which explores extremophiles, viral infection, immune system, multicellularity, development or aging in cosmic silence, and the first experimental results. The Platform also allows to observe the response of life to microgravity in absence of radiation, a key condition to explore life in space.